104k views
8 votes
Given: PO IPO

Prove:
(-o) (mat) = -1
m
PO
po
P'(-b, a)
P (a, b)
Y-Y
1.me=
PO X2-X
C-a
Q' (d.c)
Q (c,d)
Check

Given: PO IPO Prove: (-o) (mat) = -1 m PO po P'(-b, a) P (a, b) Y-Y 1.me= PO X2-X-example-1
User Barry
by
4.9k points

1 Answer

5 votes

Answer: d-b

Explanation:

Given: PO IPO Prove: (-o) (mat) = -1 m PO po P'(-b, a) P (a, b) Y-Y 1.me= PO X2-X-example-1
User Selfagency
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.